Prosurvival function of the cellular apoptosis susceptibility/importin‐α1 transport cycle is repressed by p53 in liver cancer. Issue 3 (17th July 2014) - Winkler, Juliane; Ori, Alessandro; Holzer, Kerstin; Sticht, Carsten; Dauch, Daniel; Eiteneuer, Eva Maria; Pinna, Federico; Geffers, Robert; Ehemann, Volker; Andres‐Pons, Amparo; Breuhahn, Kai; Longerich, Thomas; et al.
<x xml:space="preserve">Abstract</x> Proteins of the karyopherin superfamily including importins and exportins represent an essential part of the nucleocytoplasmic transport machinery. However, the functional relevance and regulation of karyopherins in hepatocellular carcinoma (HCC) is poorly understood. Here we identified cellular apoptosis susceptibility (CAS, exportin‐2) and its transport substrate importin‐α1 (imp‐α1) among significantly up‐regulated transport factor genes in HCC. Disruption of the CAS/imp‐α1 transport cycle by RNAi in HCC cell lines resulted in decreased tumor cell growth and increased apoptosis. The apoptotic phenotype upon CAS depletion could be recapitulated by direct knockdown of the X‐linked inhibitor of apoptosis (XIAP) and partially reverted by XIAP overexpression. In addition, XIAP and CAS mRNA expression levels were correlated in HCC patient samples (r = 0.463; P < 0.01), supporting the in vivo relevance of our findings. Furthermore, quantitative mass spectrometry analyses of murine HCC samples (p53−/− versus p53+/+) indicated higher protein expression of CAS and imp‐α1 in p53−/− tumors. Consistent with a role of p53 in regulating the CAS/imp‐α1 transport cycle, we observed that both transport factors were repressed upon p53 induction in a p21‐dependent manner. Conclusion: The CAS/imp‐α1 transport cycle is linked to XIAP and is required to maintain tumor cell survival in HCC. Moreover, CAS and imp‐α1 are targets of p53‐mediated repression, which represents a novel aspect of p53's ability to control tumor cell growth in hepatocarcinogenesis. (Hepatology 2014;60:884–895)